2015
DOI: 10.1016/j.cell.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Origin of Microtubule Dynamic Instability and Its Modulation by EB Proteins

Abstract: SUMMARY Microtubule (MT) dynamic instability is driven by GTP hydrolysis and regulated by microtubule-associated proteins, including the plus-end tracking end-binding protein (EB) family. We report six cryo-electron microscopy (cryo-EM) structures of MTs, at 3.5 Å or better resolution, bound to GMPCPP, GTPγS, or GDP, either decorated with kinesin motor domain after polymerization or copolymerized with EB3. Subtle changes around the E-site nucleotide during hydrolysis trigger conformational changes in α-tubulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

58
649
7
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(718 citation statements)
references
References 42 publications
58
649
7
4
Order By: Relevance
“…This is due to the nature of the underlying chemical kinetic processes. Growth speed fluctuations are determined by two Poisson processes, tubulin association and dissociation (23,26), whereas cap size fluctuations are additionally determined by cap site maturation, most likely the transformation of GTP (or GDP/Pi) tubulin to GDP tubulin (15,16,21). The instantaneous rate of cap site maturation depends linearly on the fluctuating cap size, resulting in a process formally similar to diffusion in a potential well (OU process).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the nature of the underlying chemical kinetic processes. Growth speed fluctuations are determined by two Poisson processes, tubulin association and dissociation (23,26), whereas cap size fluctuations are additionally determined by cap site maturation, most likely the transformation of GTP (or GDP/Pi) tubulin to GDP tubulin (15,16,21). The instantaneous rate of cap site maturation depends linearly on the fluctuating cap size, resulting in a process formally similar to diffusion in a potential well (OU process).…”
Section: Discussionmentioning
confidence: 99%
“…Maturation corresponds to a conformational change, most likely associated with GTP hydrolysis or phosphate release (15,16,19,21). The maturation rate can be experimentally determined from the characteristic length of the EB binding region and the average microtubule growth speed, a procedure called "comet analysis" (13,19,22).…”
mentioning
confidence: 99%
“…These conformational changes not only contribute to the intrinsic polymerization dynamics of microtubules but also seem crucial for microtubule-associated proteins to monitor, control, build, and modify microtubule networks [40]. Most recently, it was shown that structural plasticity is key to the modulation of microtubule dynamics by (+)-end-binding proteins since they recognize a structural state rather than a chemical state and promote compaction of the microtubule lattice, thereby facilitating GTP hydrolysis [41].…”
Section: Microtubules and Microtubule-motor Systems In Vitromentioning
confidence: 99%
“…subtomogram averaging E ukaryotic microtubules are formed by the polymerization of αβ-tubulin protein heterodimers (1)(2)(3)(4). Stabilized microtubules provide tracks for cellular cargo, and dynamic instability, the alternation between slow growth and fast shrinkage, is crucial for spindle function during mitosis (5).…”
mentioning
confidence: 99%